2014
DOI: 10.1370/afm.1690
|View full text |Cite
|
Sign up to set email alerts
|

Cost, Utilization, and Quality of Care: An Evaluation of Illinois' Medicaid Primary Care Case Management Program

Abstract: We studied costs and utilization trends, overall and by service and setting. We studied quality by incorporating Healthcare Effectiveness Data and Information Set (HEDIS) measures and IHC performance payment criteria. RESULTSIllinois Medicaid expanded considerably between 2006 (2,095,699 fullyear equivalents) and 2010 (2,692,123). Annual savings were 6.5% for IHC and 8.6% for YHP by the fourth year, with cumulative Medicaid savings of $1.46 billion. Per-beneficiary annual costs fell in Illinois over this perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…29 Our study builds on the longitudinal analysis by Kralj and Kantarevic, 30 who found that physicians who transitioned from feefor-service payment to capitation were 7% to 10% more likely to achieve cancer screening targets than those remaining in fee-for-service practice; however, in contrast to our study, theirs was a physician-level analysis and did not assess the relative influence of team-based care. Evidence from the US is mixed, whereby some studies have shown that practices that adopted components of patientcentred medical homes were more likely to provide better preventive services 11,[31][32][33][34] and chronic disease care, 11,33,34 whereas other studies showed that the rate of improvement in quality of care was no greater in patient-centred medical homes than in comparison practices. 13,35 These studies did not separate the effect of payment reform from other types of patient-centred medical home reform, such as the addition of nonphysician team members.…”
Section: Discussionmentioning
confidence: 99%
“…29 Our study builds on the longitudinal analysis by Kralj and Kantarevic, 30 who found that physicians who transitioned from feefor-service payment to capitation were 7% to 10% more likely to achieve cancer screening targets than those remaining in fee-for-service practice; however, in contrast to our study, theirs was a physician-level analysis and did not assess the relative influence of team-based care. Evidence from the US is mixed, whereby some studies have shown that practices that adopted components of patientcentred medical homes were more likely to provide better preventive services 11,[31][32][33][34] and chronic disease care, 11,33,34 whereas other studies showed that the rate of improvement in quality of care was no greater in patient-centred medical homes than in comparison practices. 13,35 These studies did not separate the effect of payment reform from other types of patient-centred medical home reform, such as the addition of nonphysician team members.…”
Section: Discussionmentioning
confidence: 99%
“…6 Payment reform is an essential element of a medical home and requires shifting physicians from fee-for-service remuneration to capitation or blended payments. 7,8 Early evidence suggests that medical homes have the potential to improve the quality of chronic disease prevention and management [9][10][11][12] and reduce medical utilization. [11][12][13] During the last decade, more than three-quarters of family physicians in Ontario, Canada, have transitioned from a traditional fee-for-service practice to a medical home that incorporates blended capitation payment and, in some cases, funding for nonphysician health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…6 Payment reform is an essential element of a medical home and requires shifting physicians from fee-for-service remuneration to capitation or blended payments. 7,8 Early evidence suggests that medical homes have the potential to improve the quality of chronic disease prevention and management [9][10][11][12] and reduce medical utilization. …”
mentioning
confidence: 99%
“…Training a career researcher in any one of the methods outlined, launching a single junior faculty in a successful focused research career, or building a sustainable organizational research enterprise with a defined research agenda takes years of effort and investment. 2,3 Are these authors proposing a bold standard, or an impossible one for all but the rare case? Or is this a brilliant, innovative, and achievable synthesis of many research methods and traditions that is not only feasible, but worthwhile-even imperative-to pursue?…”
Section: Forthcomingmentioning
confidence: 99%
“…• the medical to the social determinants of health 1 • the policies and particulars of case management programs, to their effects on people and populations 2,3 • caring for disadvantaged, disenfranchised individuals, to helping people participate in the political process 4 • designing portals to enable patients to access personal health records, to assessing how this technology can be implemented in small and medium sized practices 5 • referring to advising 6 • rigor to relevance in research 7,8 • bemoaning reductions in the contribution of family physicians to the child health workforce, to knowing some of the factors that underlie recent changes 9 • lamenting that so many people die in the hospital, to understanding how family physicians can deftly take on different roles to help terminally ill patients spend their last days in familiar surroundings 10 • depersonalized, inflexible, unsustainably expensive care in one health care system, to patient-centered, transparent, and affordable care in another system 11 • literal to meaningful translation and communication 12 • the personal turmoil of being the target of legal action, to the transcendent effects of helping another person 13 Ian McWhinney observed that a uniquely important (and often unsupported and undervalued) facet of family medicine is "an acquaintance with the particulars." 14 The articles in this issue incite the notion that personal knowledge is vital to the effectiveness of primary care.…”
mentioning
confidence: 99%